Madness and Authority in Jacobi and Ferraris: Why New Realism Is Not New - Norris, Benjamin (Stasis, 2020)
New Realism is not new. Instead of a new response to a novel philosophical problem, New Realism is an unacknowledged resurrection of Jacobi’s criticism of philosophical rationality that ignited what is now known as the “pantheism controversy.” Both Jacobi and Ferraris argue that the antirealist epistemologies of their contemporaries displace our relation to the world to which thought is supposed to be beholden. Further, both Jacobi and Ferraris claim that the antidote to these delusional philosophical ideations is realism. Finally, both take a reactionary stance toward the renegotiation of authority that stands at the core of the Enlightenment project. If this is indeed the case, then New Realism is a repetition and not an advance. More significantly, despite its own aspirations, New Realism is a reactionary, anti- Enlightenment philosophical proposal. In short, Ferraris says “Goodbye Kant!” too quickly and for old reasons.